Pembuatan Bioetanol Dari Mikroalga Limbah Cair Kelapa Sawit Dengan Variasi Konsentrasi Ragi Menggunakan Saccharomyces Cerevisiae - Sandy Juliana Sari; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Energy consumption is increasing steadily with the population growth and industrial development. Therefore, a substitute should be found. Bioethanol has been pointed out as a solution for variety complex problems related to energy and environmental issues. One of material that has potential to be used as raw material for bioethanol is microalgae. Microalgae Chlorella pyrenoidosa can be lived in wastewater, such as in palm oil mill effluent. Chlorella pyrenoidosa has been considered to be aviable and renewable feedstock for bioethanol production because it high carbohydrates contain. Chlorella pyrenoidosa is hydrolyzed into glucose for further fermented into bioethanol. This research aimed to observe the best condition on fermentation process by concentration of yeast are 10%, 15%, 20% and 25%. Measurement of bioethanol concentration using refractometer. The analysis show the highest concentration of bioethanol was 0,28% using yeast 25%.Keywords : Chlorella pyrenoidosa, hydrolysis, fermentation, bioethanol